The Influence of Organizational Culture on Employee Mental Health - Nabilla Ayu Nilamsari; Maylafayzza Farah H (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Organizational culture plays a crucial role in shaping employee mental health. This study aims to examine the relationship between organizational culture and employee mental well-being in the modern workplace. The hypothesis posits that a positive, supportive culture correlates with better mental health outcomes. A quantitative survey was conducted among 200 employees using validated psychological scales and organizational culture inventories. Statistical analysis revealed that employees in organizations with open communication, appreciation, and work-life balance programs reported lower stress and higher job satisfaction. The results highlight the importance of fostering a healthy organizational culture to promote employee well-being and organizational productivity. The study concludes that investing in positive cultural practices is essential for sustainable mental health in the workplace.